Investigating the agreement between the clinician and research diagnosis of attention deficit hyperactivity disorder and how it changes over time; a clinical cohort study. Issue 2 (11th June 2018) - Longridge, Rachel; Norman, Shelley; Henley, William; Newlove Delgado, Tamsin; Ford, Tamsin
Abstract : Background: Attention Deficit Hyperactivity Disorder (ADHD) is a common reason for referral to Child and Adolescent Mental Health Services (CAMHS), but families experience long delays between first professional contact and diagnosis, which risks development of secondary impairments. This study explores the agreement between clinician and research diagnoses of ADHD among children attending CAMHS, and their access to interventions. From the limited literature, we anticipated fluctuation and delays, but no other study has focused prospectively on ADHD diagnoses. Methods: This was a secondary analysis of a cohort of children attending two CAMHS between 2006 and 2009. The sample included 288 consecutive referrals of children aged between 5 and 11 years. Parents and teachers completed the Development and Well‐Being Assessment (DAWBA) when the child was recruited to the study, which provided the research diagnosis of ADHD from the baseline. Clinicians reported no, possible, or definite diagnosis of ADHD and interventions provided at 6‐monthly intervals for up to 2 years while the child attended CAMHS. We assessed agreement between the diagnoses using Kendall's Tau‐B. Results: Of the 101 children with a research diagnosis of ADHD, 26 received a definite clinician diagnosis during 2‐year follow‐up, and 47 received a possible clinician diagnosis. The chance‐corrected agreement was poor at all time points (Kendall's Tau‐B 0.14–0.48). Clinician diagnoses were unstable, particularly if possible ADHD was recorded at the initial assessment. Of those with a research diagnosis, 15 were prescribed medication and 11 were offered parent training. Conclusions: The use of standardised diagnostic assessments could reduce diagnostic uncertainty and increase access to evidence‐based interventions.